Stages of crisis communication in public administration. Case study Romanian Ministry of Transport - Gagu, Eleni; Rus, Mihaela; Tasențe, Tănase (Technium Social Sciences Journal, 2021)
For a democratic state to function effectively, the public administration, whether central or local, must communicate with its citizens. The emergence of a crisis can attract the attention of the public and the media, and poor communication from the public administration can threaten the trust of citizens. In this paper, we analyzed how the Romanian Ministry of Transport responded to potential crisis situations, related to good practices for crisis communication suggested by theorists in the field.